KAJIAN BENTUK DAKWAAN KOMBINASI DALAM PERKARA PENCURIAN DENGAN KEKERASAN (STUDI PUTUSAN NOMOR 591/PID.B/2021/PN SMG) - Fabianus Evan Pradityaputra (Verstek, 2023)
Abstract:This study aims to find out about the use of alternative subsidiary forms of indictment by the Public Prosecutor and the Judge's considerations in assessing and deciding cases that dropped Article 365 paragraph (3) of the Criminal Code in conjunction with Article 55 paragraph (1) 1st of the Criminal Code to the Defendants. The research method used in this research is normative legal research which is prescriptive and applied. The approach used by the author is a case approach. The types and sources of legal materials used are primary and secondary legal materials using literature/document studies, analysis techniques of legal materials using the syllogism method and interpretation using deductive logical reasoning methods. Based on the results of the research, it shows that in Decision Number 591/Pid.B/2021/PN Smg the use of alternative subsidiary combination indictments by the Public Prosecutor is by the provisions of Article 143 paragraph (2) of the Criminal Procedure Code and the fulfilment of the elements in Article 365 paragraph (3) of the Criminal Code jo Article 55 paragraph (1) 1st of the Criminal Code charged with violating the crime of theft with violence which resulted in the death of the victim.Keywords: Theft with violence, Indictment, Consideration of the Judge, Proof